Formation of the processual component of future border guard officers' readiness for physical education of personnel - A. Melnykov; L. Rybak (Kazimierz Wielki University, 2016)
The data on the state of formation of communication and organizational abilities as components of the processual component of the readiness of future border guard officers to physical education of personnel was obtained and analyzed. The study was attended by 128 cadets who were completing their studies at a specialized institution of higher education. To establish the state of formation of the procedural component of their readiness for the physical education of personnel, a questionnaire, proposed by specialists, was used. It was established that the use of the current content of physical training and the traditional approach to the organization and implementation of this process during the study allows 55.8% of graduates to achieve a high level of processual readiness for the physical education of personnel. 5.4% of future officers of the border guard service showed middle level, the rest 38.8% - low and lower than the average level of the processual readiness formation. The obtained data testify to the need to improve the organization, approaches to formation and implementation of the content of the physical training of future officers of the Border Guard Service during their study in a specialized institution of higher education. This will increase the number of graduates with high and higher than the average level of processual readiness for the physical education of personnel.